River Coastal Settlement Building Regulations on Settlement Conditions in Cikoang Village - Nurul Nadjmi; Afifah Mutiara Ramadhani Rachmat (Architectural Research Journal, 2022)
Building regulations in coastal settlements on settlement conditions in Cikoang Village. This research was conducted using quantitative analysis techniques supported by descriptive qualitative methods. The results of this study indicate that the Cikoang settlement is a coastal settlement with an elongated spatial pattern following the direction of the river so that there are rules that apply to buildings around the river but Cikoang Village does not have a defined river border, this could be due to gradual erosion of river water. to the plain surface due to the absence of embankments at the boundary. Analysis of the Cikoang Village building layout consisting of KDB, KLB, and GSB according to the formula and standard directives for RTBL Makassar City and its surroundings. Cikoang Village which is included in the research radius is classified with medium building density, namely 41 – 61 buildings/ha. The settlement orientation pattern is linear and the infrastructure facilities in Cikoang Village are sufficient and can serve the surrounding population.